2009
DOI: 10.1111/j.1365-2621.2009.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of ZnO powder‐coated PVC film to inactivate food pathogens

Abstract: In this work, the effects of two different amounts of zinc oxide (ZnO) nanoparticles on the antimicrobial activities of poly (vinyl chloride)-based films to inactivate food pathogens were investigated. Results showed that the ZnO-coated film exhibited a good inhibition effect on the growth of Escherichia coli and Staphylococcus aureus and its ability was attributed to the ZnO nanoparticles. The ZnO-coated films exhibited more effective antibacterial activity for S. aureus. However, antifungal activity of the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(136 citation statements)
references
References 32 publications
(108 reference statements)
1
120
0
Order By: Relevance
“…For example these materials have well known antibacterial properties and have been incorporated into anti-bacterial fabrics [2] and orthopaedic cements [3][4][5] with efficacy against Gram negative and Gram positive organisms [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For example these materials have well known antibacterial properties and have been incorporated into anti-bacterial fabrics [2] and orthopaedic cements [3][4][5] with efficacy against Gram negative and Gram positive organisms [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO NPs have been used as an antimicrobial agent in food packaging [33]. Antibacterial activity of ZnO NPs coated polyvinyl chloride has been observed against E. coli and S. aureus [113].…”
Section: Food Preservationmentioning
confidence: 99%
“…The label on the packages are improvised with radiofrequency identification display (RFID), this technique is able to track the food product during its transportation and distribution. Antimicrobial activity of ZnO powder coated PVC film with respect to food pathogens revealed that electrostatic interaction between bacterial cell surface and nanoparticles inhibited the growth of pathogens [22]. Nanomaterials like CNT, silicon nanowires, ZnO-nanorods etc, elevated the detection capability of biomolecules [23].…”
Section: Nanomaterials Used In Food Packagingmentioning
confidence: 99%
“…Depolarization of α-tubulin, disturbing the cellular structure, partial fragmentation of Protein [60] Silver zeolite NMs Produces reactive oxygen species [19] Carbon nanotubes Causes inflammation in neural cells (glial cells), cytokine [87] Dextran coated SPION(20nmand 60 nm) Induced proinflammatory cytokine [86] Colloidal gold NPs (1µM/5µL) Affected electrical activity in retina but no morphological changes [87] …”
Section: Nanomaterials and Parameters Tissues/cells And Responses Refmentioning
confidence: 99%